VD_FINDINFO AM 7/13 - 6/2013 vom 5. März 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, RADIATION DU RÔLE, AM, ASSURANCE-MALADIE PRIVÉE | 61 let. b LPGA, 79 al. 1 LPA-VD, 94 al. 1 let. c LPA-VD